Oligotrophy vs. copiotrophy in an alkaline and saline habitat of Lonar Lake - Nimonkar, Yogesh S.; Godambe, Tejashree; Kulkarni, Apurva; Patel, Tarachand; Paul, Dhreej; Paul, Debarati; Rale, Vinay; Prakash, Om (Frontiers in Microbiology, 2022)
In the current study, we tried to conduct a comparative study on Oligotrophic versus Copiotrophic microorganisms from a hyper-alkaline and saline habitat of Lonar Lake, located in the Buldhana district of Maharashtra, India. Cell number of oligotrophic and copiotrophic microorganisms from sediment was enumerated using an array of nutrient-rich and oligotrophic mediums and simulated natural conditions by the three-tube MPN method. Total 50-strains from 15-different genera and 30-different species were cultivated from the highest positive dilutions of different enrichments to identify the taxa of oligotrophs and copiotrophic microorganisms dominating in Lonar Lake. True oligotrophs were not isolated because they adapted to higher C levels during isolation and changed their lifestyle. On the contrary, several true copiotrohs, which couldnot not adapt and survive on low carbon medium were isolated. In addition, it was also observed that changes in medium composition and nutrient level altered the selection of organisms from the same initial sample. Furthermore, low carbon level and its quick depletion from oligotrophic medium, worked as a limiting factor inducing cell death after 2-3 generations. The study indicated that copiotrophic microorganisms dominated the eutrophic Lonar lake. Metagenomics studies also supported our findings of oligotrophic and copiotrophic strains, which showed capability of producing industrially important enzymes. The strains adapted to the two lifestyles for balancing the influx of carbon/nutrients into the lake ecosystem. It was also observed that longterm supply of low levels of carbon, followed by isolation on enriched media can serve as a good strategy in isolation of novel taxa of oligotrophs, having industrial or environmental importance.